How Does Metacognitive Knowledge Potential Impact on the Academic Success of Prospective Science Teachers? - Muhammad Asy'ari; Saiful Prayogi; Taufik Samsuri; Muhali Muhali (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Metacognition generally has two essential components: metacognitive knowledge and metacognitive awareness. Unfortunately, research that focuses on and explores the description of metacognitive knowledge and its implications for the academic success of prospective science teacher students is still rare. The current study aimed to explore (1) the baseline levels of metacognitive knowledge (MK) among prospective science teachers (PST), (2) the relationship between the extent of MK and academic success, and (3) the potential differences in MK based on gender. The correlational research with the survey method was used in the study. The study involved 206 (male: 93 and female: 113) prospective science teachers who participated in a fundamental physics course at Mandalika University of Education as a sample. Data on MK was collected using twenty items of essay tests that are valid and reliable to collect PSTs’ MK. In contrast, PSTs’ learning success data was collected using instruments used in mid-semester examinations and practical laboratory test results. The data was further analyzed descriptively and statistically using the ANOVA and Pearson correlation tests. The result shows that PSTs’ MK is in the low category (MK<60). Additionally, male prospective science teachers demonstrated better declarative (mean: 59.247; p < 0.05) and procedural knowledge (mean: 64.482; p < 0.05) indicators, and MK positively correlates in each indicator. Based on the findings, it is evident that PSTs' MK significantly differs between males and females, the positive correlations between MK indicators, and potentially impact teaching practices and cognitive outcomes. Furthermore, future research needs to develop effective interventions, learning models, and instructional practices to enhance metacognitive skills and science learning outcomes in teacher education.